Do designated market makers provide liquidity during a flash crash? - Mario Bellia; Kim Christensen; Aleksey Kolokolov; Loriana Pelizzon; Roberto Renò (Leibniz Institute for Financial Research SAFE, 2022)
We show that (electronic) designated market makers are not necessarily beneficial to the stock market during ash crashes. They actually consume liquidity when it is most needed, even if they are rewarded by the exchange to provide immediacy. This behavior exacerbates the transient price impact, unrelated to fundamentals, typically observed during a ash crash. In their place, slow traders provide liquidity, taking advantage of the discounted price. We thus uncover a trade-off between the greater liquidity and efficiency provided by designated market makers in normal times, and the disruptive consequences of their quoting/trading activity during distressed times.
Keywords: G10; G14; 330; flash crashes; designated market makers (DMMs); high-frequency traders (HFTs); market fragility